2020
DOI: 10.1016/j.ijpara.2019.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of hookworm prevalence in southern India using environmental parameters derived from Landsat 8 remotely sensed data

Abstract: Soil-transmitted helminth infections propagate poverty and slow economic growth in low-income countries. As with many other neglected tropical diseases, environmental conditions are important determinants of soil-transmitted helminth transmission. Hence, remotely sensed data are commonly utilised in spatial risk models intended to inform control strategies. In the present study, we build upon the existing modelling approaches by utilising fine spatial resolution Landsat 8 remotely sensed data in combination wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…In this study, both increased vegetation (NDVI) and elevation were associated with increased odds of infection as well as an increase in intensity of infection. In another study using remotely sensed data at a fine resolution in Jawadhu Hills, topographical parameters of elevation and slope were negatively and positively associated with hookworm infections at the village level [ 58 ]. Riess et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, both increased vegetation (NDVI) and elevation were associated with increased odds of infection as well as an increase in intensity of infection. In another study using remotely sensed data at a fine resolution in Jawadhu Hills, topographical parameters of elevation and slope were negatively and positively associated with hookworm infections at the village level [ 58 ]. Riess et al .…”
Section: Discussionmentioning
confidence: 99%
“…In this study, both increased vegetation (NDVI) and elevation were associated with increased odds of infection as well as an increase in intensity of infection. In another study using remotely sensed data at a fine resolution in Jawadhu Hills, topographical parameters of elevation and slope were negatively and positively associated with hookworm infections at the village level [58]. Riess et al have shown that ecological variables are associated with hookworm infection but have differing effects within a geographical region, are scale-dependent and urge caution against prediction at smaller scales using large-scale data [52].…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%
“…The random forest approach was chosen because it can deal with continuous outcome data, multicollinear predictor variables, and low numbers of training samples, and hence, it is the recommended machine learning method for generating predictions [ 26 ]. It has been successfully applied in similar studies [ 10 , 11 , 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…Several improvements have recently been suggested to common modeling methods applied to smaller sub-national spatial extents. These include utilizing fine resolution RS data (e.g., Landsat 8), employing a larger number of relevant environmental indicators derived from the spectral bands (e.g., modified normalized difference water index [MNDWI]), and using a variable distance radius to extract and aggregate environmental indicator variables around point-prevalence locations [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although up to now the knowledge about the factors that influence canine parasite infections in cities has been scarce (Tull et al 2019;Otero et al 2018), it is known that the presence and spread of parasites in urban populations is related mainly to socioeconomic conditions (Amundson Romich 2008; Kulinkina et al 2020). The presence of parasites is associated with poverty, inefficient health systems, illiteracy, overcrowding (Pinto et al 2016), poor hygiene, poor housing, limited access to safe water and inadequate rubbish disposal (Álvarez Di Fino et al 2020).…”
Section: Introductionmentioning
confidence: 99%